Setting of import tolerances for difenoconazole in various crops - European Food Safety Authority (EFSA); Giulia Bellisai; Giovanni Bernasconi; Luis Carrasco Cabrera; Irene Castellan; Monica delAguila; Lucien Ferreira; Luna Greco; Samira Jarrah; Renata Leuschner; Andrea Mioč; Stefanie Nave; et al. (EFSA Journal, 2025)
Abstract In accordance with Article 6 of Regulation (EC) No 396/2005, the applicant Syngenta Crop Protection AG submitted an application to the competent national authority in Spain (rapporteur Member State, RMS) to set import tolerances for the active substance difenoconazole in various crops imported from the United States and Brazil. The data submitted in support of the request were found to be sufficient to derive maximum residue level (MRL) proposals for citrus fruits, tree nuts, mangoes, papayas, dry peas and soya beans. Adequate analytical methods for enforcement are available to control the residues of difenoconazole in the commodities under consideration, animal tissues and eggs at the validated limit of quantification (LOQ) of 0.01 mg/kg and in milk at the validated LOQ of 0.005 mg/kg. Quick, Easy, Cheap, Effective, Rugged, and Safe (QuECHERs) methods are also available for the determination of difenoconazole alcohol (CGA205375) in animal matrices at the validated LOQ of 0.012 mg/kg. Based on the risk assessment results, EFSA concluded that the short‐term and long‐term intake of residues resulting from the use of difenoconazole according to the reported agricultural practices is unlikely to present a risk to consumer health.